2009
DOI: 10.1680/geot.2007.00063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relative density on plate loading tests on fibre-reinforced sand

Abstract: Plate load tests were carried out on un-reinforced sand and sand reinforced with fibres, compacted at relative densities (DR) of 30%, 50% and 90%. For the reinforced sand, 24 mm long polypropylene fibres were added, a concentration of 0·5% by dry weight. The analysis of the results indicates that the soil load-settlement behaviour is significantly influenced by the fibre inclusion, changing the kinematics of failure. The best performance was obtained for the densest (DR = 90%) fibre-sand mixture, where a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 12 publications
2
17
0
7
Order By: Relevance
“…The authors also tested this mixing procedure in the field with results that corroborate the tests performed in the laboratory (e.g. Consoli et al 2009). 2.…”
supporting
confidence: 58%
“…The authors also tested this mixing procedure in the field with results that corroborate the tests performed in the laboratory (e.g. Consoli et al 2009). 2.…”
supporting
confidence: 58%
“…Compared to conventional improvement methods using reinforcement, fibers have some advantages like prevention of potential weak planes which mostly form parallel to plane oriented reinforcement and conservation of isotropic shear strength characteristics [1]. e reinforced soil behavior of fibers was studied by researchers in the last decades, but focusing the problem only under static conditions [2][3][4][5]. It was revealed that using fiber reinforcement in soil increased the shear strength of soil and improved the ductile behavior and reduced the strength loss observed after the peak strength was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Consoli et al [4] and Consoli et al [14] focused on consolidated drained triaxial tests to examine the ber reinforcement e ect on the mechanical behavior of sand admixed with varying cement content. Specimens with a relative density of 70% were prepared, and empirical equations to determine peak and residual strength based on cement content, ber content, and con ning pressure were proposed in Consoli et al [4] and Consoli et al [14]. e resistance to liquefaction in ber-reinforced soils increased the number of cycles required to cause liquefaction under undrained loading conditions [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a large number of experiments have been conducted to investigate the mechanical behavior of fiber reinforced soil, including triaxial compression test (Consoli et al, 1998(Consoli et al, , 2005(Consoli et al, , 2007a; Kaniraj and Gayathri, 2003;Hendry et al, 2014), unconfined compression test (Kaniraj and Havanagi, 2001;Tang et al, 2007;Olgun, 2013;Consoli and Bassani, 2010;Yi et al, 2015;Kumar and Gupta, 2016), direct shear test (Prabakar and Sridhar, 2002;Yetimoglu and Salbas, 2003;Cai et al, 2006;Consoli et al, 2007a), ring shear test (Casagrande et al, 2006;Consoli et al, 2007b), plate load test (Consoli et al, 2003a(Consoli et al, , 2003b(Consoli et al, , 2009, CBR test (Yetimoglu et al, 2005), tensile test (Consoli et al, 2011;Divya et al, 2013;Li et al, 2014;Viswanadham et al, 2010;Tang et al, 2015a,b;Correia et al, 2015), swelling test (Viswanadham et al, 2009), desiccation test (Miller and Rifal, 2004;Tang et al, 2012) and other tests (Gray and Ohashi, 1983;Gray and Maher, 1989;Nataraj and McManis, 1997;Santoni and Webster, 2001;Michalowski and Cermak, 2003;Tang et al, 2010;Liu et al, 2011;…”
Section: Introductionmentioning
confidence: 99%